DENSIFIKASI PEMUKIMAN PENDUDUK NAGARI LUBUK BASUNG SEMENJAK MENJADI IBU KOTA KABUPATEN AGAM - Ardino, Ardino; Bakaruddin, Bakaruddin; Juita, Erna (STKIP PGRI Sumbar, 2013)
This research aims to determine the residential densification Nagari Lubuk Basung Since be Agam regency capital. This research is descriptive. The population in this study were all heads of families who settled in villages Lubuk Basung as a whole amounted to 11 237 households. Samples were taken in two ways, the samples were taken by purposive sampling areas (designation) the reason being that these areas have the highest KK and an area adjacent to public places such as markets and terminal regions, namely: the Old Market Jorong Lubuk Basung and the sample of respondents drawn with random sampling technique the proportion of 5% by the number of respondents 99 heads of families. The research found that: (1) the population settlement pattern Nagari including rare Lubuk Basung before and after a solid, and the spur to reach the location before very easily before, the state of human settlements is less good before and after the nice, orderly condition before and after the settlement is more regular, (2) The population density Nagari including rare Lubuk Basung before and after more dense, often before not society activities and post more often, unfavorable social conditions before and after the nice, cozy comfort of the public before and after the much less comfortable. (3) Income before residents Nagari Lubuk Basung Rp 740,000 - Rp 1.550.000/month and after Rp 1.551.000 - 2.361.000/month. (4) The public is able to meet the educational needs of the family before and after Being Agam regency capital, the view of the formal education before and after the poor better, note the lack of education for children before and after more attention, formal education before and after the child there, the number of children dropouts also declined, before so many children capital after graduating junior high and high school and college in general. (5) with the community prior to Become Capital Agam substandard and after a smooth, poor road conditions before and after be good, but has not been considered so that the connecting road connecting the streets smoothness remained at levels quite smoothly.